Excessive computer use as an oral health risk behaviour in 18‐year‐old youths from Poland: A cross‐sectional study - Dorota Olczak‐Kowalczyk; Jacek Tomczyk; Dariusz Gozdowski; Urszula Kaczmarek (Wiley, 2019)
Abstract Background Many studies have indicated that the excessive use of computers (more than 3 hr/d) might be associated with an unhealthy life‐style. Aim The aim of this study was to evaluate the relationship between excessive computer use with the condition of the teeth and periodontium and the oral health behaviour of 18‐year‐olds. Design Cross‐sectional studies, using a questionnaire, were carried out on 1,611 18‐year‐olds from Poland. The questionnaire contained questions about socioeconomic status and information about health‐related behaviour. The condition of their teeth and gingivae were clinically assessed. Results Excessive (>3 h/d) computer use was reported by 492 (31%) of participants, who had an increased frequency of unfilled cavities (1.97 vs. 2.27, p = .047) and a higher risk of oral hygiene neglect (e.g., using dental floss 41% vs. 34%, p = .009). Excessive computer use was also seen to be associated with poor dietary habits. Individuals who declared excessive computer use also had a higher risk of gingival bleeding (35% vs. 29%, p = .009). Conclusion In the group studied, excessive computer use by adolescents constituted a risk factor for neglect of oral hygiene, poor dietary choices, and failure to benefit from oral health care. Therefore, these aspects should be included in the risk assessment of oral disease and incorporated into educational programs that promote a healthy lifestyle.